THE EFFECT OF STUDENT'S LEARNING INTEREST ON EYE COMPETENCY METAL CASTING ENGINEERING LECTURE DURING THE COVID-19 PANDEMIC - Panujuh, Panujuh; Sukrawan, Yusep; Komaro, Mumu (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the effect of student interest in learning on the competence of metal casting engineering courses during the covid-19 pandemic. This research design uses a descriptive research type with a quantitative approach. This study uses samples from Mechanical Engineering Education Students class of 2017 and 2018. Students have carried out online learning using the zoom meeting application in the Metal Casting Engineering course during the covid-19 pandemic with a total sample of 36 people. The results of this study are that the student's interest in learning and the competence of mechanical engineering education students in metal casting engineering courses during the covid-19 pandemic are in the high category. There is a positive and significant relationship and influence between student interest in learning and the competence of metal casting engineering courses during the covid-19 pandemic.